Dietary magnesium and migraine in adults: A cross‐sectional analysis of the National Health and Nutrition Examination Survey 2001–2004. Issue 2 (27th January 2021) - Slavin, Margaret; Li, Huilun; Khatri, Manisha; Frankenfeld, Cara
Abstract: Background: Clinical trials have demonstrated magnesium supplements to be effective for prophylactic treatment of migraine. Dietary magnesium intake of many Americans is known to be below nutritional recommendations, but typical magnesium intake from dietary sources in adults with migraine has not previously been evaluated. Objective: This study aimed to quantify dietary and total (diet + supplement) magnesium consumption of adults with migraine or severe headache in the United States, and to investigate the relationship between magnesium consumption levels and prevalence of migraine or severe headache. Methods: This analysis included cross‐sectional data from 3626 participants, 20‐ to 50‐years old in the National Health and Nutrition Examination Survey between 2001 and 2004. Presence of migraine or severe headache in the past 3 months was determined by questionnaire. Individuals responding affirmatively were classified as having migraine, and individuals reporting not experiencing migraine or severe headache were classified as controls. Dietary magnesium intake was determined from a 24‐hour recall interview, supplemental magnesium intake was determined from the dietary supplements interview, and total magnesium intake was the sum of dietary and supplement intake. Results: Mean dietary consumption of magnesium was below the recommended dietary allowance (RDA) for both migraine ( n  = 905) and control groups ( n  = 2721). Attainment of the RDA through a combination of diet and supplements was associated with lower adjusted odds of migraine (odds ratio [OR] = 0.83, 95% confidence intervals [CIs] = 0.70, 0.99, p  = 0.035). Magnesium consumption in the highest quartile (Q) was associated with lower odds of migraine than in the lowest Q for both dietary (OR = 0.76, 95% CI = 0.63, 0.92, p  = 0.006) and total (OR = 0.78, 95% CI = 0.62, 0.99, p  = 0.042) magnesium intake in adjusted models. Conclusion: These results suggest inadequate consumption of magnesium intake is associated with migraine in U.S. adults ages 20–50. Further prospective investigations are warranted to evaluate the role of dietary magnesium intake on migraine.